Who Qualifies for Rights? : Homelessness, Mental Illness, and Civil Commitment - Failer, Judith Lynn (Cornell University Press, 2018)
When does a person become disqualified for some or all of the rights associated with full citizenship? Who does qualify for rights? When mental health workers took Joyce Brown from her "home" on a New York City sidewalk and hospitalized her against her will, she defended herself by asserting her rights: to live where she wanted, to speak to the press to deride the city's policy, and to refuse unwanted psychiatric treatment. In theory, as a United States citizen, Brown possessed rights protecting her from governmental intrusion into her personal life. In practice, those rights were curtailed at the time of her civil commitment. Using the case of Joyce Brown as an example, Judith Lynn Failer explores the theoretical, legal, and practical justifications for limiting the rights of people who are involuntarily hospitalized. By looking at the reasons why law and theory say that some people diagnosed with mental illnesses no longer qualify for the full complement of constitutional rights, the author pieces together basic assumptions about who does, and who should, qualify for rights. Failer's analysis is motivated by her concern that people facing involuntary hospitalization stand to lose the most effective means they have of protecting themselves from abuse-their rights. She concludes that there is insufficient guidance for deciding who qualifies for regular rights and full citizenship. Finally, the author calls for the use of flexible standards to determine who should and who does qualify for rights.